ANTIBACTERIAL ACTIVITY AND CHEMICAL COMPOSITION OF THE ESSENTIAL OIL OF Aloysia aloysioides Loes - Castro Mandujano, Nino (2022)
In the present investigation the essential oil of the "lime-lime" (Aloysia aloysioides Loes and Moldenke) was studied, it was collected in the district of Tintay, Apurímac-Peru, the inhabitants of this area, use it for its anti-inflammatory properties in the form of plasters. The objective is to extract and characterize the essential oil of Aloysia aloysioides Loes & Moldenke and evaluate the antibacterial activity. From 674 grams of fresh sample (branches) the essential oil was obtained by steam distillation, then it was characterized by performing a physicochemical analysis, chromatographic by GC-MS, spectroscopic FT-IR and antibacterial analysis. The essential oil was obtained with a yield of 0.38%; β-Caryophyllene (10.88%), limonel (9.9%), p cymene (7.22%), caryophyllene oxide (5.98%), Nerolidol (4.96%) and α-humulene were identified (4.92%) as majority components. In addition, this essential oil has antibacterial activity against Staphylococcus aureus, up to a 73% effectiveness close to gentamicin; for these reasons it could be used in pharmaceutical preparations